Kinetics and sperm morphometry in sexed and conventional frozen semen of Brown Swiss bulls - Ormachea Valdez, Edwin (2019)
The aim of this study was to determine the kinetics and sperm morphometry in sexed and conventional frozen semen of Brown Swiss bulls using the Integrated Sperm Analisys system. Ten straws of sexed semen and 10 straws of conventional semen imported from USA were used. The values of kinetics (curvilinear velocity [VCL], average velocity [VAP], rectilinear velocity [VSL], amplitude of lateral head displacement [ALH], beat frequency [BCF], linearity index [LIN [, index of straightness [STR], oscillation index [WOB]) and sperm morphometry (area, length, width and perimeter of the head of the sperm) were similar between sexed and conventional semen of Brown Swiss bulls frozen in straws.